2014
DOI: 10.1182/blood-2014-05-576835
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of FcγR-mediated phagocytosis by IVIg is independent of IgG-Fc sialylation and FcγRIIb in human macrophages

Abstract: Key Points Phagocytosis of IgG-opsonized blood cells by human macrophages is inhibited by intravenous immunoglobulins. This inhibition is independent of IgG-Fc sialylation but improves with IgG preparations that bind FcγRs more avidly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
94
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(104 citation statements)
references
References 45 publications
10
94
0
Order By: Relevance
“…Monocyte-derived macrophages were cultured for 9 days with either macrophage colony-stimulating factor (M-CSF) or granulocyte-macrophage colony-stimulating factor (GM-CSF) from monocytes isolated from heparin blood of healthy controls, as previously described. 8 …”
Section: Preparation Of Blood Leukocytes and Monocyte-derived Macrophmentioning
confidence: 99%
See 1 more Smart Citation
“…Monocyte-derived macrophages were cultured for 9 days with either macrophage colony-stimulating factor (M-CSF) or granulocyte-macrophage colony-stimulating factor (GM-CSF) from monocytes isolated from heparin blood of healthy controls, as previously described. 8 …”
Section: Preparation Of Blood Leukocytes and Monocyte-derived Macrophmentioning
confidence: 99%
“…1,6 However, splenic macrophages have been poorly characterized thus far in humans, especially with regard to FcgR expression. Functional studies of IgG-mediated phagocytosis in humans often use monocyte-derived macrophages instead 7,8 because they are readily available. However, because it is not well known whether these macrophages are similar to splenic macrophages, the relevance of such studies can be debated.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 All blood was obtained after informed consent and according to the 1964 Declaration of Helsinki. splenocytes) under various conditions.…”
Section: Isolation Of Human Neutrophils and Monocytesmentioning
confidence: 99%
“…Bone marrow neutrophils were isolated from femurs of 2-to 4-month-old mice, using a Percoll gradient as previously described, 26 and were resuspended at 5 3 10 6 /mL in cold Hank balanced salt solution (HBSS) containing Ca 21 and Mg …”
Section: Phagocytosis Experiments In Mice In Vitromentioning
confidence: 99%
“…These findings are in keeping with data suggesting that different degrees of Fc multimerization are required to elicit FcgR and complement-mediated effects. For example, recent studies revealed the dimeric fraction of IVIG has increased ability of blocking Fc-FcgR interaction over IVIG monomers in macrophage phagocytosis, and a separate report suggested that C1q activation required the formation IgG hexamers (40,41). Consistent with these findings, whereas both lower-and higher-order fractions of GB4542 demonstrated decreased ADCP effect at higher concentrations, decreased CDC activity was observed only in the presence of high concentration of higher m.w.…”
Section: Discussionmentioning
confidence: 71%